The Influence Of The Government's Role In Building Digital Economic Growth In Indonesia (Study Case: Bakso Ceker Vitho) - Mica Siar Meiriza; Gracella Rosnah S Hutagalung; Ade Mima Zakia Siregar; Muhammad Ilham Fiqri; Novia Grace Cristin Limbong; Serly Sahfitri (Jurnal Scientia, 2024)
Indonesia's young population and technical innovations are driving the country's quickly growing digital economy, and government programs are essential in assisting micro, small, and medium-sized businesses (UMKM). Despite obstacles including a lack of capital and a poor digital infrastructure, these companies make a substantial contribution to economic growth. Through a qualitative method and a review of the literature, this study seeks to understand how government policies affect UMKM's digital expansion in Indonesia and offer a thorough framework that takes business players' viewpoints into account. Interviews with Bakso Ceker Vitho's owner, Surya, provided information on how UMKM might adjust and prosper in the online market. Bakso Ceker Vitho exhibits successful tactics, including the use of platforms like GoFood and GrabFood to broaden market reach, a structured ordering system, and a variety of payment alternatives, including QRIS. In summary, Bakso Ceker Vitho's ability to successfully adjust to digital problems emphasizes how important digital transformation is for SMEs. Long-term success in the digital age will be supported by sustained investment in influencer relationships, CRM systems, data analytics, and a varied menu, all of which will improve consumer engagement and visibility.